2003
DOI: 10.1515/epoly.2003.3.1.644
|View full text |Cite
|
Sign up to set email alerts
|

On the key role of the interface in the cationic polymerisation of p-methoxystyrene in miniemulsion

Abstract: This paper presents the latest improvements, in terms of reactivity and molar masses, of the process of cationic polymerisation of p-methoxystyrene in miniemulsion, which was published previously [Cauvin et al., Macromolecules 2002, 35, 7919]. The formulation was adapted to change dramatically the specific surface and the polarity of the interface where the polymerisation takes place. Adding hexadecane permits to significantly decrease the particle diameter and thus to favour a faster polymerisation rate. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(42 citation statements)
references
References 13 publications
(25 reference statements)
7
35
0
Order By: Relevance
“…The authors explained this stability by the formation of small oligomers through rapid initiation by DBSA, as soon as the system is ultrasonicated, thus acting as hydrophobes and suppressing Ostwald ripening. In an other study, adding hexadecane enabled the same authors 18 to significantly decrease the particle diameter and thus favor a faster polymerization rate. In our case, the initiatior pMOS-HCl is post-added.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The authors explained this stability by the formation of small oligomers through rapid initiation by DBSA, as soon as the system is ultrasonicated, thus acting as hydrophobes and suppressing Ostwald ripening. In an other study, adding hexadecane enabled the same authors 18 to significantly decrease the particle diameter and thus favor a faster polymerization rate. In our case, the initiatior pMOS-HCl is post-added.…”
Section: Resultsmentioning
confidence: 94%
“…Some other studies were also performed in the same vein with phosphonic acids instead of sulfonic acids. 16 Cauvin et al 17,18 recently showed that, using dodecylbenzenesulfonic acid (DBSA) as inisurf in a miniemulsion process, polymerization of pMOS proceeded without the need for Yb(OTf) 3 . Although poly(pMOS) average molar mass increases with conversion, a "controlled" active center generation could not be put forward.…”
Section: Introductionmentioning
confidence: 99%
“…For ionic polymerizations, inisurfs were molecular surfactants in which the polar head was a strong acid or base [33][34][35][36]. Thus the counter ions (proton or hydroxide) were involved in the initiation of polymerization.…”
Section: )mentioning
confidence: 99%
“…Consequently, the polymerization was carried out in conditions that may not be those of completely rigorous miniemulsion polymerization. Cationic polymerization of p-methoxystyrene was initiated by the use of dodecylbenzenesulfonic acid which acted as an inisurf [35,36]. The authors demonstrated that the addition of a hydrophobe could be avoided.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation